Sustainability and Corporate Strategy in the Azerbaijan Banking Sector: The Role of Green Finance - Orujov, Samir (ADA University, 2025)
There has been a structural shift within the world's financial system during the last decade, driven increasingly by sustainability and climate resilience drivers. This shift is most observable in national banking systems' green finance strategic reorientation nowhere else as well as in our country. This thesis examines the Azerbaijan banking sectors interlink between sustainability and company strategy, particularly the changing role of green finance both as a regulatory imperative and strategic option. While green finance is a very active topic worldwide through instruments like the EU Taxonomy (Council 2020) and IFRS Sustainability Disclosure Standards (I. S. Board 2023), its localized definition and application in developing and transition economies remains largely unexplored. Azerbaijan, a rich hydrocarbon upper-middle-income country (worldbank 2020), has the singular challenge of reconciling its carbon-footed past economy with ambitions towards a sustainable and diversified financial system. It is being driven by the Central Bank of the Republic of Azerbaijan (CBAR) (CBAR, sustainable-finance n.d.), which has issued guidelines and frameworks to include environmental, social, and governance (ESG) in financial oversight, risk management, and credit extension. This study integrates qualitative and quantitative sources, qualitative information is derived from expert interviews, while quantitative findings are based on secondary statistical data from Central Bank of Azerbaijan's Sustainable Finance Survey Reports (2023 and 2024) and comprises an extensive literature review with thematic content analysis of Azerbaijani bank CEOs' CEO, regulatory official, and sustainability officer interviews. It has two purposes: (1) an examination of the degree to which the sustainability principles inform firm strategy in the Azerbaijani banking industry, and (2) an exploration of the degree of effectiveness as well as green finance practice maturity in the industry. The research draws on three theoretical underpinnings: Stakeholder Theory, which posits that banks must become more attentive to broader social and environmental expectations; Institutional Theory, which addresses the influence of norms, regulation, and mimetic pressures on organizational action; and the Resource-Based View (RBV), with its emphasis on internal resources and innovation as a source of competitive advantage. The theories enable multidimensional analysis of drivers, barriers, and implications of integration of sustainability into banking strategy. Early observations, based on a wide reading of policy reports, regulatory papers, and ESG reports, find Azerbaijan's banking industry to be in an emerging but gaining momentum stage of embracing sustainability. CBAR's Supervisory Review and Evaluation Process (SREP) and climate stress test project are the regulatory milestones that say it all for this nation. The partially covered by commercial banks falls behind in adoption, though. Institutional resistance to change, lack of domestic expertise, and the unavailability of environment-specific green taxonomies are generally identified as impediments. Banks that have embraced green credit products, ESG risk ratings, and digital sustainability platforms, however, enjoy reputational gains, enhanced investor confidence, as well as greater alignment with international development finance best practices. This research contributes to the scholarship of the academic community in sustainable banking with one of the pioneering empirical research studies in Azerbaijan—a market that has been largely overlooked in the global ESG conversation. It provides action guidance to policymakers who want to bridge the regulatory intent-institutional preparedness gap, and banking CEOs who want to infuse sustainability into their strategic DNA without compromising profitability or resilience. Lastly, the research argues that green finance is no longer an extremist agenda but part of Azerbaijan's banking's strategic vision in the long run. But if sustainability has to be converted into practice, it not only needs to be driven through policy but also through profound organizational change, inter-sectoral collaboration, and ongoing capacity building.
Keywords: Green finance.; Sustainable banking.; Environmental, social, and governance (ESG) investing.; Banks and banking -- Environmental aspects.; Sustainable development -- Finance.; Climate change mitigation -- Economic aspects.; Financial institutions -- Environmental policy.